2016
DOI: 10.7863/ultra.15.11028
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Ureteral Stent Removal in Women

Abstract: The proposed method for ureteral stent removal in women under ultrasound guidance was shown to be faster and to have lower visual analog pain scale scores, in comparison with removal by a cystoscope, which makes it an attractive option for outpatient urologic praxis in uncomplicated cases, and because it is free of the risk of ionizing radiation and more comfortable, it can be used in pregnant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Cystoscopy, a widely used method for replacing ureteral stents, involves passing a rigid or flexible tube (with a lens and camera at the end) through the urethral sheath, which may be painful for the patient. To address this problem, other stent replacement methods have been reported (2,(4)(5)(6). These include the guidewire lasso technique, the snare technique, the crochet hook technique, and the cystoscopic direct grasping technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystoscopy, a widely used method for replacing ureteral stents, involves passing a rigid or flexible tube (with a lens and camera at the end) through the urethral sheath, which may be painful for the patient. To address this problem, other stent replacement methods have been reported (2,(4)(5)(6). These include the guidewire lasso technique, the snare technique, the crochet hook technique, and the cystoscopic direct grasping technique.…”
Section: Discussionmentioning
confidence: 99%
“…The guidewire lasso and gooseneck snare techniques require extra equipment and are difficult to perform, so fluoroscopy time is inevitably long. Gadzhiev et al reported that the snare technique, under ultrasound guidance, also requires practice and special skills (5). The cystoscopic direct grasping technique uses forceps located inside the cystoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Вестник урологииVestnik Urologii 2024;12(2):76-86 блей. Если у женщин процедура извлечения стента не представляет особых сложностей и может быть выполнена при помощи спирали[24], то у мужчин требует применения ригидного или гибкого цистоскопа, а в некоторых случаях манипуляция может быть выполнена только под общей анестезией в связи с выраженной болью. Данная процедура связана с затратами на визит…”
unclassified